Hedging using credit default swap options: an empirical study on the data of an American energy company - Maitham Rabie Hadi; Haidar Abdull Jaber Al-Sarai (Iraqi Journal for Administrative Sciences, 2025)
The global economy has entered the third millennium, called the era of globalization, loaded and influenced by a range of international financial and economic variables, that was and stilled and will continue to have a radical and profound impact in the performance of financial institutions of all types and classifications from the perspective that financial institutions which is playing a vital role in economic activity. Moreover, the multiplicity of activities and the work of financial institutions make them facing new risks did not used to encounter before, threat of credit or default still obsessed with every financial institution for being associated with the man job of the majority of financial institutions which is credit, despite the economic reforms and protocols are setting by international agencies. However, the work of these financial institutions in the credit sector is still exposed to default risk. On this basis, the study came to highlight the most important management tools of default risk which credit default swaptions and detected the effectiveness of hedging in terms of risk and return for a user of these contracts in the hedge default risk. The study has based on the daily spreads of CDS contract for the company (Nexen Inc.),Which is the most active company in the CDS market, for the period from (20/03/2013) until (20/09/2013). So the problem of the study focused on a number of questions and the most important of which are: 1. Is the using of CDS contracts as a strategy to hedging of default risk better than of non-hedged case at all? 2. Is the Black model accurate in the pricing of European options on credit default swaps? 3. Is the hedging by use European options on CDS contracts rising the hedging effectively for CDS contracts? The study found a number of conclusions such as: 1. The use of CDS contracts as the strategy to hedge the risk of default is much better than a case of non-hedge at all. Through the findings of the test results, it shows that in the case of non-hedge at all, the investor is exposed to the tragic loss represented by the loss of the entire amount of investment in the event of default. But when the investor uses a strategy of buying credit default swaps, it can recover the face value of the bonds at an event of default enabling it's to reinvestment and achieving of earnings. 2. The Black model is the accurate one in the pricing of European options contracts on credit default swaps. 3. Most of the options strategies emphasized that the use of European options on CDS contracts rise to hedging effectively for CDS contracts. Thus, a credit default swaptions contract is a more effective tool in hedging than CDS contracts. Obviously, the study found a nmber of recommendations, including: 1. The use of credit default swaps for hedging default risk rather than non-hedged case at all. 2. The need to depend on the Black model by dealers in the pricing of European options on credit default swaps because of its accuracy and reality. 3. The need to use the European options on credit default swaps because of it is ability to increase the benefits of these contracts and the most important of it's the possibility of avoiding unfavorable movements of spread with the exploitation of favorable movements in spread.